Plectranthus amboinicus essential oil and carvacrol bioactive against planktonic and biofilm of oxacillin- and vancomycin-resistant Staphylococcus aureus - Sara Edwirgens Costa Benício Vasconcelos; Hider Machado Melo; Theodora Thays Arruda Cavalcante; Francisco Eduardo Aragão Catunda Júnior; Mário Geraldo de Carvalho; Francisca Gleire Rodrigues Menezes; Oscarina Viana de Sousa; Renata Albuquerque Costa (BMC, 2017)
Abstract Background The emergence of multidrug-resistant bacteria is a worldwide concern and in order to find an alternative to this problem, the occurrence of antimicrobial compounds in Plectranthus amboinicus essential oil was investigated. Thus, this study aims to determine susceptibility of Staphylococcus aureus isolated from food to antibiotics, P. amboinicus essential oil (PAEO) and carvacrol. Methods Leaves and stem of P. amboinicus were used for extraction of essential oil (PAEO) by hydrodistillation technique and EO chemical analysis was performed by gas chromatography coupled to a mass spectrometer. S. aureus strains (n = 35) isolated from food and S. aureus ATCC 6538 were used to evaluate the antimicrobial and antibiofilm activity of PAEO and carvacrol. All strains (n = 35) were submitted to antimicrobial susceptibility profile by disk diffusion method. Determination of MIC and MBC was performed by microdilution technique and antibiofilm activity was determined by microtiter-plate technique with crystal violet assay and counting viable cells in Colony Forming Units (CFU). Results Carvacrol (88.17%) was the major component in the PAEO. Antibiotic resistance was detected in 28 S. aureus strains (80%) and 12 strains (34.3%) were oxacillin and vancomycin-resistant (OVRSA). From the 28 resistant strains, 7 (25%) showed resistance plasmid of 12,000 bp. All strains (n = 35) were sensitive to PAEO and carvacrol, with inhibition zones ranging from 16 to 38 mm and 23 to 42 mm, respectively. The lowest MIC (0.25 mg mL−1) and MBC (0.5 mg mL−1) values were observed when carvacrol was used against OVRSA. When a 0.5 mg mL−1 concentration of PAEO and carvacrol was used, no viable cells were found on S. aureus biofilm. Conclusion The antibacterial effect of carvacrol and PAEO proves to be a possible alternative against planktonic forms and staphylococcal biofilm.